Bottom-up and top-down development: nexus between asset-based community development and unconditional cash transfers. Issue 1 (2nd January 2022) - Reddy, Geeta; Barbalat, Guillaume
ABSTRACT: This review explores the potential for a conjunction between Asset-Based Community Development (ABCD) and Unconditional Cash Transfers (UCT) to intensify development outcomes. ABCD is a community-driven, bottom-up development model that focuses on empowering the poor. UCT is a centralised, top-down, income distribution programme critical in alleviating poverty. Following an overview of the principles, main outcomes, and critiques of these two different development approaches, we present how ABCD and UCT could support one another to improve development. We base our theory upon the fact that both methods can work in a synergistic manner and palliate each other's weaknesses.